1998
DOI: 10.1023/a:1024461920456
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to duty‐related incident stressors in urban firefighters and paramedics

Abstract: Little is known about the variables that might be associated with posttraumatic stress symptomatology in high-risk occupational groups such as professional firefighters and paramedics. A sample of 173 urban professional firefighter/EMT's and firefighter/paramedics rated and ranked the stressfulness of 33 actual and/or potential duty-related incident stressors. They also reported whether they had experienced each of these incident stressors within the past 6 months and, if they had, to recall on how many occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(106 citation statements)
references
References 8 publications
3
101
1
1
Order By: Relevance
“…Critical incident stress includes, but is not limited to, responding to the death of a child, 1,2 providing care to friends, family or those known to the responder, 2-6 and treating acutely ill or seriously injured patients. 2,4,7,8 Additional stressors associated with the provision of care include the risks of exposure to blood-borne pathogens, 9-11 verbal or physical violence, 7,12,13 and injury or death from vehicle-related crashes. [14][15][16] To a lesser extent, other research efforts have found that paramedics may also experience chronic work-related stressors, including insufficient salaries, 17,18 conflict with administrators, 17,19,20 lack of support from or conflict with colleagues, 2,3,5,[17][18][19][20][21] and interference with nonwork-related activities.…”
Section: Introductionmentioning
confidence: 99%
“…Critical incident stress includes, but is not limited to, responding to the death of a child, 1,2 providing care to friends, family or those known to the responder, 2-6 and treating acutely ill or seriously injured patients. 2,4,7,8 Additional stressors associated with the provision of care include the risks of exposure to blood-borne pathogens, 9-11 verbal or physical violence, 7,12,13 and injury or death from vehicle-related crashes. [14][15][16] To a lesser extent, other research efforts have found that paramedics may also experience chronic work-related stressors, including insufficient salaries, 17,18 conflict with administrators, 17,19,20 lack of support from or conflict with colleagues, 2,3,5,[17][18][19][20][21] and interference with nonwork-related activities.…”
Section: Introductionmentioning
confidence: 99%
“…Firefighters have unique preconditions to develop working relationships and emotional connections, and higher degrees of work cohesion have been found to be significantly associated with decreased anxiety during emergencies. Other positive effects are successful decision making, greater effectiveness in responding to emergencies, a greater ability to cope with post-emergency experiences, and increased psychological well-being (Beaton, Murphy, Johnson, Pike, & Cornell, 1998;Fullerton, McCarroll, Ursano, & Wright, 1992;Landen & Wang, 2010;North et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Support should also be made available during and after the placement period, accounting for immediate or delayed responses to any event(s) encountered. Encouraging education and awareness of mental health issues among paramedic students is an important step in reducing the high rates of anxiety, depression, PTSD and suicide that have been noted among qualified staff (25)(26)(27)(28)(29)(30)(31)(32)(33). Introducing the concept of support and education early on, may also lead to a gradual change in the culture of the paramedic workforce, encouraging access to peer support and associated supports such as the Victorian Ambulance Crisis Counselling Unit.…”
Section: Discussionmentioning
confidence: 99%